PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUASAN ANGGOTA KOPERASI SIMPAN PINJAM KARYA MURNI MEDAN - Saragih, Nawary (UNIKA Santo Thomas, 2019)
The purpose of this study was to determine the effect of the marketing mix of services on the satisfaction of members of the Cooperative Savings and Loans Work Purely Medan